(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the critical connection between physics and environmental sustainability, emphasizing the role of physics education in fostering eco-consciousness among students. By linking core physics concepts to real-world environmental issues—such as energy conservation, renewable energy, pollution control, and climate change—the article highlights how physics can equip students with the knowledge and tools needed to tackle ecological challenges